Literasi Keuangan dan Pendapatan pada Keputusan Investasi dengan Perilaku Keuangan sebagai Variabel Moderasi - Panjaitan, Nutia Feby Hanes; Listiadi, Agung (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The main objective of this study is to obtain empirical evidence of the effect of financial literacy and income on investment decisions with financial behavior as a moderating variable in students of the accounting education faculty of economics, State University of Surabaya. The variables in this study. study. The research conducted is (1) Financial Literacy (2) Income 3) Financial Behavior (4) Investment Decisions. This study uses multiple regression analysis and moderation regression. The population in this study were active students of accounting education at the State University of Surabaya. The sampling method used was purposive sampling and obtained 123 respondents. The data collection technique in this study used an online questionnaire with a Likert scale and the data analysis technique used was multiple linear regression with the help of the SPSS version 23 software program. The results of this study indicate that financial literacy affects investment decisions, income has no effect on investment decisions, behavior finance moderates the effect of financial literacy on investment decisions and financial behavior cannot moderate the effect of income on investment decisions